Fluid Inclusion Analysis for Constraining the Hydrocarbon Accumulation Periods of the Permian Reservoirs in Northeast Ordos Basin - 陈刚 李书恒 章辉若 杨甫 丁超 雷盼盼 胡延旭 (Journal of earth science (Wuhan, China), 2013)
Geochronology of hydrocarbon accumulation and reconstruction is an important and challenging subject of petroleum geology in multi-cycle superimposed basin. By fluid inclusion （FI） analysis combined with the apatite fission track （AFT） modeling thermal path of the FI host rock, a case study of constraining the hydrocarbon accumulation and reconstruction periods of the Permian reservoirs in Northeast Ordos Basin （OB） has been conducted. The FI homogenization temperatures of the oil-gas-bearing sandstone core-samples from the Lower to Upper Permian reservoirs statistically present two groups with a low and a high temperature peaks in ranges of 90-78 and 125-118 ℃, re- spectively, corresponding to 2-stage primary hydrocarbon accumulations of the Early-Middle Mesozoic. Besides, there exists another group with a medium-high peak temperature of 98 ℃ in the Upper Per- mian reservoirs, corresponding to the hydrocarbon reconstruction and destruction of the Late Meso- zoic to Cenozoic. According to the projected ages of the FI peak temperatures on the AFT thermal path of the FI host rocks, it is further induced that there experienced 3-stage hydrocarbon accumulations in the Permian reservoirs during the Mesozoic to Cenozoic. These are： （1） all the various primary hydro- carbon Permian reservoirs together developed 2-stage accumulations of 162-153 and 140-128 Ma in agreement with the multi-cycle subsidence burial heating process of the basin; （2） the Upper Per- mian reservoirs further experienced 1-stage secondary hydrocarbon accumulation and re- construction at ca. 30 Ma in coincidence with a critical tectonic conversion of the slow to rapid uplifting process from the Late Cretaceous to Neogene.